Japan-India Relations in the Light of India’s Look-East Policy: Strengthening the Kizuna - Borah, Rupakjyoti (WILAYAH: The International Journal of East Asian Studies, 2015)
Japan and India have long historical ties, which date back to the times when the monk, Bodhisena went to Japan and Buddhism spread in that country from the land of its birth, India, However, the two countries veered off during the period of the Cold War as they were on the opposite sides of the divide - Japan is an ally of the United States while India was close to the erstwhile Soviet Union. That, however, did not prevent India from supplying iron ore to Japan in the period after the end of the Second World War, which greatly helped Japan’s reconstruction efforts. The relations between India and Japan have improved remarkably fast after the end of the Cold War so much so that the two countries are now “Special Strategic and Global Partners”. Unlike most countries in Asia, Japan and India have no historical differences. Japan is the only country (apart from Russia) with which India has an annual bilateral summit. The paper will attempt to analyse the main areas of convergence and divergence between Japan and India. It examines the extent to which things have changed in the relationship following the launch of the “Look-East Policy” in the early 1990s. Last, but not the least, it attempts to lay down a roadmap for the future of Indo-Japanese ties.